Yannick Boswinkel, Labouring With Large Stones. A Study into the Investment and Impact of Construction Projects on Mycenaean Communities in Late Bronze Age Greece. - Dickinson, Oliver (Journal of Greek Archaeology, 2023)
pp. 195, 44 figures (25 colour), 42 tables, 6 appendices. Leiden: Sidestone Press, 2021. ISBN 978-94-6428-010-4 (hardcover); 978-94-6428-009-8 (softcover), £40; 978-94-6428-011-1 (e-book). £120 hardcover, £40 softcover.